2019
DOI: 10.14499/indonesianjpharm30iss2pp114-121
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective effects of Curcumin-Mesoporous Silica Nanoparticles on CCl 4 -induced Hepatotoxicity Wistar rats

Abstract: It has been reported that curcumin has a hepatoprotective effect, but its low solubility limited its utilization. Recently there was so many emerging research of advanced curcumin formulation, such as nanoparticles curcumin. In our previous study, curcumin has been loaded into mesoporous silica nanoparticles (C-MSN). This study was performed to evaluate of C-MSN hepatoprotective effect in CCl4-induced rats. Sixteen rats were divided into four groups, namely normal and CCl4 control, curcumin, C-MSN group. Treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
3
1
Order By: Relevance
“…The results of scoring degeneration, leukocyte infiltration, and necrosis in this study were not in accordance with the research conducted by Hadisoewignyo et al [48], where the curcumin group had a lower score than the curcumin modified into nanosized particles group, although it was not statistically significant. In this study, it was concluded that nanocurcumin with mesoporous silica nanoparticles carriers had been widely reported to cause toxicity.…”
contrasting
confidence: 93%
“…The results of scoring degeneration, leukocyte infiltration, and necrosis in this study were not in accordance with the research conducted by Hadisoewignyo et al [48], where the curcumin group had a lower score than the curcumin modified into nanosized particles group, although it was not statistically significant. In this study, it was concluded that nanocurcumin with mesoporous silica nanoparticles carriers had been widely reported to cause toxicity.…”
contrasting
confidence: 93%
“…73 In several studies, 3-aminopropyltriethoxysilane (APTES) was employed as an amine functionalization agent on the surface of MSNs, and Cur was then loaded onto the amine functionalized-MSNs. 62,63 Hartono et al synthesized cubic MSNs (particle size and pore size around 100 and 10 nm, respectively) and mesoporous silica micronsized-particles (MSM) that were functionalized with 3-aminopropyltriethoxysilane (APTES) and then Cur was encapsulated within amine functionalized-MSN and MSM (Fig. 2).…”
Section: Amine-functionalized Msnsmentioning
confidence: 99%
“…The author of this study didn't explore the effect of MSNs in a separate group, thus it's unclear whether the increased number of necrotic hepatic cells in the Cur loaded-MSNs group was due to MSN toxicity or the high concentration of Cur. 63 Cur has been shown to have cardioprotective effects in rats with myocardial necrosis via inhibiting free radical production in rats with myocardial ischemia. 136 Yadav et al investigated the cardioprotective effects of free Cur and Cur loaded-MSNs against doxorubicin-induced myocardial toxicity in rats.…”
Section: Biological Activity Of Cur-loaded Msnsmentioning
confidence: 99%
See 1 more Smart Citation